A Sociolinguistic Analysis of Code-switching and Code-mixing in Radio and Online Advertisement Jingles in Nigeria - Oso, Mary; Babalola, Emmanuel (International Journal of Language and Literary Studies, 2025)
The study of the linguistic phenomena of code-switching and code-mixing has been extended from conversations and music to advertisement jingles because multilingual codes are needed in advertisement jingles to reach or meet the intensely multilingual and multicultural nature of the Nigerian society without which, effective transferring of information about products and services to the diverse categories of people in the Nigerian society would be futile and just a waste of time. The objectives of this study are to identify the types of code-switching used in the selected Southwestern Nigerian Radio advertisement jingles and Online advertisement jingles and to find out the most dominant type of code-switching used in the advertisement. The primary source of data was drawn from 60 code-switched advertisement jingles collected from 30 radio commercials and 30 online advertisements on YouTube through purposive random sampling technique. The 30 radio jingles were collected from 12 radio stations in the Southwestern states in Nigeria which are Osun, Oyo, Ondo, Ogun, Ekiti and Lagos. In each of the states, a private radio station and a public radio station were selected. The design of the study is both quantitative and qualitative. It is quantitative because it showed the frequency of occurrence of the types of code-switching which is determined through simple percentile and quantitative because it discussed the reasons why the advertisers used the types of code-switching. The results showed that the three types of code-switching were present in the advertisement jingles with 129 (43%) instances of inter-sentential code-switching, 162 (54%) instances of intra-sentential code-switching and 8 (3%) instances of tag switching. Intra-sentential code-switching was prominently used by the advertisers which reflect their high level of bilingual proficiency and their linguistic skills of unifying codes in ensuring an effective dissemination of information to the listeners. The study recommended that these linguistic practices of code-switching and code-mixing should be used by advertisers when marketing their products and services so as to solve the challenge of multilingualism in the context of advertising.